Ligno Sulphonate [SLS] Laboratory Testing For the Recovery of Residual Oil at Ledok Oil Field - Edi Untoro; Purnomosidi Purnomosidi; Slamet Priyanto (Politeknik Energi dan Mineral Akamigas, 2021)
Fossil energy much still needed and exhalated in demand every year on industrial sector, household, and transportation in Indonesia. In the other hand, oil gas production has decreases as many of oil and gas reservoirs have saturated with water breakthrough. Therefore, Enhance Oil Recovery [EOR] as one of proposed solution is adopted to optimize the remaining reserves of oil wells exploitation, especially from mature field that has lesser production capacity towards production problems. Ledok field Cepu district, Central Java Indonesia has many mature wells that produce liquids with its water cut higher than 90 %. The objective of study is to determine which variables that are involve on black liquor or Sodium Ligno Sulphonate [SLS] application as surfactant for EOR on laboratory measurements. Core flooding measurements had been developed and measured. Crude, formation water, and SLS surfactant were injected into the artificial cores. FTIR test show appearance of Sulphonate and Ether alkyl in its composition. Preliminary results show the surfactant has optimum performance to recover oil up to 79% with IFT value 10-1 dyne/cm.